Mining tailings severely impact plant communities in a rainforest watershed - Fernandes, G. Wilson; Ramos, Letícia; Justino, Wénita de Souza; Kenedy-Siqueira, Walisson; Figueiredo, João Carlos Gomes; Oki, Yumi; Goulart, Fernando Figueiredo; dos Santos, Rubens Manoel; Viana, João Herbert Moreira; Nunes, Yule Roberta Ferreira; Aguilar, Ramiro; Poorter, Lourens; et al. (Anthropocene, 2025)
The collapse of a mining tailings dam in 2015 drastically affected a large area of an already threatened Atlantic Forest along the Rio Doce in Brazil. We evaluated the interactions between edaphic and floristic factors in impacted and reference sites to understand how the impact of the tailings affected the riparian plant communities along the river. The species richness of the adult and sapling strata was, respectively, 46.4 % and 61.5 % lower in the impacted sites relative to the reference sites. A similar pattern was observed for both species and phylogenetic diversity. We also recorded large changes in species composition in the adult and sapling strata in impacted sites relative to the reference sites along the river. These negative changes in the plant community were correlated with drastic increases in soil iron and phosphorus concentration, and fine sand proportion, and decreases in the proportion of carbon and coarse sand in the sites impacted by the mining tailings. We observed a close relationship between plant composition in both the adult and sapling strata with edaphic factors. The alterations in species composition triggered by the deposition of mining tailings may induce significant shifts in ecosystems, potentially prompting numerous tipping points throughout the river basin, as indicated by the different sapling species, some of which are invasive species of highly difficult eradication. These altered forests might suffer from impoverishment, dominated by a limited species set, some of which could expand its distribution upon neighboring, already threatened, regions. Such expansion could exacerbate the degradation of the Rio Doce watershed to a point of no return to the previous condition. [Display omitted] •Impacted sites showed reduced species richness and diversity.•Significant changes in plant composition linked to soil alterations.•Edaphic factors closely related to plant composition shifts.